Evaluating practical functions of available web-based virtual museums using qualitative comparative method - Moien, Rostamian; Barkeshli, Mandana (Common Ground Publishing LLC, Illinois, USA, 2015)
By the extension of digital networks and the rise of personal computers, advantages of information technology have been noticed by major cultural organizations such as museums. As the result, different versions of online virtual museums have been created so far with various approaches and technologies. In addition to having a short review on literature and the history of web-based virtual museum development, this paper evaluates the practical functions of available web-based virtual museum development approaches using the qualitative comparative method regarding general aims, functions, and concepts in the definition of a museum defined by the International Council of Museums (ICOM). Considering the findings of this study, it is possible to increase effectiveness and efficiency of virtual museums.